Application of response surface methodology to optimize biodiesel production from esterification of palmitic acid in excess methanol - Hiep, Dang Tan; Chen, Bing-Hung (Vietnam Journal of Science and Technology, 2014)
The main purpose of this study was to find out optimal conditions for producing biodiesel via esterification of palmitic acid in excess methanol using solid acid catalyst, viz. Amberlite™ IR-120 (H) resin. A stepwise regression for Box-Behnken design was performed to optimize parameters of this process. A 93.94% of conversion efficiencies could be explained by an insignificant lack-of-fit response surface model (R2 = 0.9394; p = 0.259). Optimum conditions were found as follows: 8:1 in the molar feed ratio of methanol to palmitic acid, a reaction temperature as 61.0 °C, a reaction time of 11.73 h. The catalyst loadings and agitation speed were kept constant at 10 wt.% of palmitic acid and 600 rpm, respectively. Under these conditions, conversion efficiency of palmitic acid to palmitic acid methyl ester reaction is (97.60 ± 0.64)%, and it is nearly 0.19% difference between observed and predicted values. The solid catalyst can be reused at least five times after treating in a simple way.